Rationale and design of the multiethnic Pharmacogenomics in Childhood Asthma consortium. (July 2017) - Farzan, Niloufar; Vijverberg, Susanne J; Andiappan, Anand K; Arianto, Lambang; Berce, Vojko; Blanca-López, Natalia; Bisgaard, Hans; Bønnelykke, Klaus; Burchard, Esteban G; Campo, Paloma; Canino, Glorisa; Carleton, Bruce; et al.
Aim: International collaboration is needed to enable large-scale pharmacogenomics studies in childhood asthma. Here, we describe the design of the Pharmacogenomics in Childhood Asthma (PiCA) consortium.Materials & methods: Investigators of each study participating in PiCA provided data on the study characteristics by answering an online questionnaire.Results: A total of 21 studies, including 14, 227 children/young persons (58% male), from 12 different countries are currently enrolled in the PiCA consortium. Fifty six percent of the patients are Caucasians. In total, 7619 were inhaled corticosteroid users. Among patients from 13 studies with available data on asthma exacerbations, a third reported exacerbations despite inhaled corticosteroid use. In the future pharmacogenomics studies within the consortium, the pharmacogenomics analyses will be performed separately in each center and the results will be meta-analyzed.Conclusion: PiCA is a valuable platform to perform pharmacogenetics studies within a multiethnic pediatric asthma population.